27-Deoxyactein prevents 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin-induced cellular damage in MC3T3-E1 osteoblastic cells. Issue 6 (12th May 2018) - Suh, Kwang Sik; Choi, Eun Mi; Jung, Woon-Won; Park, So Young; Chin, Sang Ouk; Rhee, Sang Youl; Pak, Youngmi Kim; Chon, Suk
ABSTRACT: 2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) is a well-known environmental contaminant that exerts its toxicity through a variety of signaling mechanisms. The present study evaluated the effects of 27-deoxyactein, one of the major constituents isolated from Cimicifuga racemosa, on TCDD-induced toxicity in osteoblastic MC3T3-E1 cells. TCDD reduced cell survival, markedly increased apoptosis, and enhanced autophagy activity. However, pre-treatment with 27-deoxyactein attenuated all TCDD-induced effects and significantly decreased intracellular calcium (Ca 2+ ) concentrations, the collapse of the mitochondrial membrane potential (MMP), the level of reactive oxygen species (ROS), and cardiolipin peroxidation compared to the TCDD-treated controls. Additionally, TCDD-induced increases in the levels of aryl hydrocarbon receptor (AhR), cytochrome P450 1A1 (CYP1A1), and extracellular signal-regulated kinase (ERK) were significantly inhibited by 27-deoxyactein. The mRNA levels of superoxide dismutase (SOD), ERK1, and nuclear factor kappa B (NF-κB) were also effectively restored by pre-treatment with 27-deoxyactein. Furthermore, 27-deoxyactein significantly increased the expressions of genes associated with osteoblast differentiation, including alkaline phosphatase (ALP), osteocalcin, bone sialoprotein (BSP), and osterix. Taken together, the present findings demonstrate the preventive effects of 27-deoxyactein on TCDD-induced damage in osteoblasts.